WAYS BY INVESTING BUSINESSES IN THE CONDITIONS OF GLOBALIZATION - Охріменко, І. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Current state of the economy and instability of enterprises investment development requires economic growth in conditions of globalization processes. Consequence of economic globalization is the internationalization of industrial relations in high-tech activities on the basis of foreign direct investment and rapid emergence of financial markets. The national economy has vast investment opportunities; but macroeconomic instability and lack of legal safeguards for the protection of the invested funds are necessary to implement an effective investment strategy. Thus; in the context of globalization and increasing global competition; an important tool of economic activity is investment. However; there is a problem of shortage of investment resources in this state. The reasons for this can be grouped into two groups. The first group relates to macroeconomic regulation of the economy; in particular; the policy of the national Bank on the formation of credit and discount rate for the loan policy of the government in creating a favorable investment climate; enterprise development and maintenance of effective judicial system. The second group of reasons relates to the level of enterprises. Among them; notably; investment tools; through which the company attracts investments and manages them. Such instruments primarily include Bank lending and management.